Influence of wall porosity and surfaces roughness on the steady performance of an externally pressurized hydrostatic conical bearing lubricated by a Rabinowitsch fluid - Walicka, Anna; Walicki, Edward; Jurczak, Paweł; Falicki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the influence of both the bearing surfaces roughness as well as porosity of one bearing surface on the pressure distribution and load-carrying capacity of a curvilinear, externally pressurized, thrust bearing is discussed. The equations of motion of a pseudo-plastic Rabinowitsch fluid are used to derive the Reynolds equation.
Keywords: pseudo-plastic fluid; Rabinowitsch model; curvilinear and conical thrust bearings; porous layer; Christensen roughness